2007
DOI: 10.1093/eurheartj/ehm033
|View full text |Cite
|
Sign up to set email alerts
|

Increase in serum adiponectin concentration in patients with heart failure and cachexia: relationship with leptin, other cytokines, and B-type natriuretic peptide

Abstract: Cachexia in HF is associated with an increase in adiponectin concentration. This may represent preservation of the physiological response to change in body fat but might also suggest that adiponectin plays a role in the pathogenesis of cachexia. The correlation between BNP and adiponectin also raises the possibility that the former might increase the secretion of the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
121
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(142 citation statements)
references
References 37 publications
14
121
1
6
Order By: Relevance
“…The use of siRNA against C/EBPa in 3T3-L1 cells clearly induces a reduction of adiponectin expression (Vernochet et al 2010). Interestingly, patients with heart failure, who develop cachexia, also present higher levels of adiponectin (McEntegart et al 2007), and in cancer cachexia patients, this parameter is robustly correlated with body weight loss ( Batista Jret al 2012). On the other hand, leptin secretion, which has been shown to be positively correlated with fat cell size, decreased by 50% 14 days after tumour cell inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of siRNA against C/EBPa in 3T3-L1 cells clearly induces a reduction of adiponectin expression (Vernochet et al 2010). Interestingly, patients with heart failure, who develop cachexia, also present higher levels of adiponectin (McEntegart et al 2007), and in cancer cachexia patients, this parameter is robustly correlated with body weight loss ( Batista Jret al 2012). On the other hand, leptin secretion, which has been shown to be positively correlated with fat cell size, decreased by 50% 14 days after tumour cell inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…High plasma levels of adiponectin observed in pts with established CHF were associated with poor prognosis and mortality. Reduced renal clearance could account for higher adiponectin concentration in CHF pts [34]. In haemodialysis pts low plasma adiponectin levels were associated with pre-existing CVD and predicted mortality outcomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of adiponectin may simply reflect the hyper-catabolic state in severe heart failure. 40 McEntegart et al 43 have recently shown that adiponectin levels are increased in patients with heart failure in the presence of cachexia. Therefore, it is necessary to clarify whether increased levels of adiponectin may be involved in the pathogenesis of heart failure or if they simply reflect the degree of cachexia in these patients.…”
Section: Obesity and Adiponectinmentioning
confidence: 99%
“…Therefore, it is necessary to clarify whether increased levels of adiponectin may be involved in the pathogenesis of heart failure or if they simply reflect the degree of cachexia in these patients. 43 Recombinant adiponectin may have a beneficial role in the therapeutic treatment and prevention of cardiovascular diseases in the future. 9,29,39 conclusion Adiponectin is a key adipokine, which participates in many metabolic activities and its levels are reduced in obese people.…”
Section: Obesity and Adiponectinmentioning
confidence: 99%